Philosophical Sonata - Byčko, Ada (Problemos, 1983)
The philosophical purport in the creative work by M. K. Čiurlionis (1875-1911), a Lithuanian composer and artist, is revealed. An attempt is made to look into misunderstanding of M. K. Čiurlionis’ innovatory contribution to art by some of his contemporaries. The features of “untraditional character”, profound “humanity”, “vitality” in his works reflected the artist’s original attitude to the world, that was ultimately conditioned by the content of the epoch (end of 19th and beginning of 20th centuries) as well as by the search for new ways for social protest against national oppression of the Lithuanian people.